A review of the spider-attacking Polysphincta dizardi species-group (Hymenoptera, Ichneumonidae, Pimplinae), with descriptions of seven new species from South America - Pádua Diego G; Sääksjärvi Ilari E; Spasojevic Tamara; Kaunisto Kari M; Monteiro Ricardo F; Oliveira Marcio L (PENSOFT PUBLISHERS, 2025)
The Neotropical Polysphincta dizardi species-group is revised. We describe seven new species from South America: P. bonita sp. nov., P. cosnipata sp. nov., P. inca sp. nov., P. macroepomia sp. nov., P. organensis sp. nov., P. pichincha sp. nov., and P. teresa sp. nov. In addition, we provide a diagnosis and an identification key to all species of the group.